The modernization of the state budget system and its role in activating supervision of the performance of government units in Algeria - HIRECH FAYZA; TORCHI MOHAMED (IJRDO - Journal of Social Science and Humanities Research, 2020)
The objective of this study is to clarify the need to adopt the performance control method and to examine the appropriateness of the modernization of the general budget system in Algeria in order to achieve the objectives of performance control, which is the result of the modernization and modernization of the General Accounting System in Algeria, Which seeks to unify international accounting and financial practices, to make financial information more credible and to provide the transparency required to rationalize public expenditure by activating oversight of the performance of government units. The study concluded with a number of conclusions and recommendations, the most important of which is that the modernization project of the general budget system in Algeria came to adopt the method of balancing programs and performance, which is in line with the basis of merit adopted by the modernization of the public accounting system, as well as the use of accounting branches such as liability accounting and cost accounting, A fundamental demand imposed by modern trends in the control of the performance of government units.